عرض تاريخي لبعض أدوات السياسة المالية العثمانية مع بيان دور المؤسسات المصرفية والأوقاف النقدية العثمانية في تمويل الأفراد والمؤسسات A Historical Review for Some of the Tools of the Ottoman Financial Policy, With a Clarification of the Role of Banking Institutions and Ottoman Cash Endowments in Financing Individuals and Institutions - khair, abdalrhman (International Journal of Al-Turath In Islamic Wealth and Finance, 2020)
يهدف هذا البحث إلى إلقاء الضوء على بعض الآليات المستخدمة من قبل الدولة العثمانية لتمويل نفقاتها المختلفة مع بيان تاريخ نشوء وتطور المؤسسات المصرفية و الأوقاف النقدية في الأراضي العثمانية ودورهما في تمويل الأفراد والمؤسسات. إذ قام الباحث ببيان الأسس الاقتصادية العامة والنظم الضريبية وبعض أدوات السياسة المالية في الدولة العثمانية وما ترتب على ذلك من مشاكل مالية ونقدية وسياسية، كما عمل هذا البحث على بيان تاريخ المؤسسات المصرفية و الأوقاف النقدية في الدولة العثمانية وإيضاح دورهما في تمويل الاحتياجات المالية للدولة والأفراد. وبعد استقصاء المؤسسات المصرفية والأوقاف النقدية ظهر للباحث أن الدولة العثمانية كانت تحتوي على نظام تمويل مزدوج (تقليدي/إسلامي)، إذ كانت الدولة العثمانية تعتمد على النظام التقليدي ممثلا بالصرافين المحليين والبنوك وإصدار أدوات الدين في تمويل احتياجاتها المختلفة وخاصة وقت الحروب والأزمات المالية، أما الأفراد فقد كانوا يعتمدون على النظام التقليدي المتمثل في الصناديق الوطنية لتمويل احتياجاتهم الزراعية، وعلى مؤسسات الأوقاف النقدية الإسلامية لتمويل احتياجاتهم الروحية كبناء المساجد وتسبيل المياة، أو تمويل تجاراتهم المتعددة. Abstract This research aims to shed light on some of the financial tools used by the Ottoman Empire to finance its various expenses, with a clarification of the history and development of banking institutions and monetary endowments in the Ottoman lands and their roles in financing individuals and institutions. This research explained the general economic fundamentals, tax systems and some debt instruments used by the Ottoman Empire and the financial, monetary and political problems that resulted from it, this research also worked on explaining the history of banking institutions and monetary endowments in the Ottoman state and clarifying their roles in financing the needs of the state and individuals. After inspecting the banking institutions and monetary endowments, it appeared to the researcher that the Ottoman state had a dual financing system (traditional/Islamic), as the Ottoman state depended on the traditional system represented by local money changers, banks and the issuance of debt instruments to finance its various needs, especially in time of wars and financial crises, as for individuals, they depended on the traditional system represented in the national funds to finance their agricultural needs, and on the Islamic endowment institutions to finance their spiritual needs such as building mosques and waterways, or financing their multiple trades. Key words: Ottoman Empire, Cash Endowments (Waqfs), Banking Institutions, Ottoman Bank, Moneychangers.